2014
DOI: 10.1007/s12072-014-9596-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel 2-step approach combining the NAFLD fibrosis score and liver stiffness measurement for predicting advanced fibrosis

Abstract: The novel 2-step approach further reduced the number of patients requiring a liver biopsy whilst maintaining the accuracy to predict advanced fibrosis. The combination of NFS and LSM for all patients provided no apparent advantage over using either of the tests alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 21 publications
3
49
0
3
Order By: Relevance
“…Recently, Chan et al . of Malaysia proposed a two‐step approach combining the NFS with LSM to predict advanced fibrosis . They reported that a two‐step approach using LSM only for patients with indeterminate and high values of the NFS to predict advanced fibrosis allowed the number of liver biopsies performed to identify patients with advanced fibrosis to be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chan et al . of Malaysia proposed a two‐step approach combining the NFS with LSM to predict advanced fibrosis . They reported that a two‐step approach using LSM only for patients with indeterminate and high values of the NFS to predict advanced fibrosis allowed the number of liver biopsies performed to identify patients with advanced fibrosis to be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been tested in various patient populations with viral hepatitis . However, such data for NAFLD are scarce, and FibroMeter is rarely used in existing studies . The current study represents one of the largest histological series to test the combined performance of transient elastography and FibroMeter in NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…In the same cohort, use of VCTE with cutoffs <8kpa and >17kpa, the negative predictive value and positive predictive values were higher, 98.2 and 89% respectively. 60 A strategy based on concordant results (e.g. low NAFLD fibrosis and low stiffness) was proposed.…”
Section: A Comparison Of Radiology Markers: In a Study Examining 2d mentioning
confidence: 99%